Analysis of Multiple Solvation Interactions of Methotrexate and Ammonium Based Ionic Liquids Using COSMO-RS. (2016) - Lotfi, Meysam; Moniruzzaman, Muhammad; Mutalib, M.I. Abdul; Wilfred, Cecilia Devi; Alitheen, Noorjahan Banu; Goto, Masahiro
Abstract: Solubility prediction of methotrexate (a pharmaceutical compound) in ammonium based ionic liquids has been investigated in this study using COSMO-RS. We examined the effect of anion and related interaction energies (misfit, H-bonding and van der Waals interaction energy) on the solubility of methotrexate (MTX) in ammonium based ionic liquids. COSMO-RS model is a physically admissible computational procedure and favorably it doesn't need the experimental data, so these traits make COSMO-RS a superior and practicable replacement for solubility calculations in ionic liquids. Our promising results showed that the methotrexate solubility highly depends on anionic part of ionic liquids, also we found out that the H-bonding interaction energy is the most controlling interaction for ionic liquids which is pursued by misfit and van der Waals interaction energy. This work results may be significant to improve our comprehending of solute solubility interactions in ionic liquids.